2014
DOI: 10.1177/0091026014535181
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Organizational Health as a Mediator for Job Expectations

Abstract: The comparison between self-expectations and perceived situations of one organization usually affects people's perception of work. The present study proposes that perceived organizational health is a mediator for the relationships between job expectations and job self-efficacy, and between job expectations and job satisfaction. Also, job self-efficacy plays a mediating role between perceived organizational health and job satisfaction. The questionnaires were developed for Chinese participants. Data were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Previous studies have shown employee expectations to be related to various employee outcomes such as job involvement, job satisfaction, organizational commitment, distress, and turnover intentions (Ashforth and Saks, 2000;Buckley et al, 1998;Major et al, 1995;Meng et al, 2014;Nelson and Sutton, 1991;Turnley and Feldman, 2000;Wanous et al, 1992). In this context, met expectations are also likely to affect work motivation (Wanous et al, 1992).…”
Section: Employee Expectations and Intrinsic Motivationmentioning
confidence: 99%
“…Previous studies have shown employee expectations to be related to various employee outcomes such as job involvement, job satisfaction, organizational commitment, distress, and turnover intentions (Ashforth and Saks, 2000;Buckley et al, 1998;Major et al, 1995;Meng et al, 2014;Nelson and Sutton, 1991;Turnley and Feldman, 2000;Wanous et al, 1992). In this context, met expectations are also likely to affect work motivation (Wanous et al, 1992).…”
Section: Employee Expectations and Intrinsic Motivationmentioning
confidence: 99%
“…In some cases, these items measure the overall feeling through multiple questions (e.g., Brewer & Selden, 1998; Cho & Lee, 2011; Daley, 2007; Kim, 2012; Kim & Wright, 2007; Ryu, 2014; Taylor, 2013). In other cases, they measure different facets of job satisfaction (e.g., Alavi & Askaripur, 2003; Alotaibi, 2001; Chih, Yang, & Chang, 2012; Meng, Zhang, & Huang, 2014). The Federal Employee View Point Survey (United States Office of Personnel Management), which has been used by some studies in our final sample (e.g., Caillier, 2012, 2013; Cho & Perry, 2012; Cho & Sai, 2013; Choi, 2009), measures job satisfaction in terms of both overall feeling and specific facets.…”
Section: Job Satisfaction In the Public Sectormentioning
confidence: 99%
“…Further, McHugh et al (2003) identified indices (financial, structural, strategical, cultural and/or behavioral) to measure health in the organization. After conducting an extensive literature review, it was observed that the concept has clarity when financial parameters (Cooper and Cartwright, 1994; McHugh and Brotherton, 2000; McHugh et al , 2003), strategical perspective (MacIntosh et al , 2007; Nair, Kumar and Ramalu, 2014; Xenidis and Theocharous, 2014; Nair, Ramalu and Kumar, 2014) and behavioral perspective (Salanova et al , 2012; Kipfelsberger et al , 2016; Meng et al , 2014) are discussed but requires further investigation to understand the factors of organizational health from structural and cultural perspective. Also, none of the researchers have been able to incorporate all these measures of organizational health together in an operational definition and neither has bridged the gap in the conceptualization of organizational health for business sector.…”
Section: Theoretical Backgroundmentioning
confidence: 99%